Ramsay Hunt Syndrome Associated with Central Nervous System Involvement in an Adult - Tommy L. H. Chan; Ana M. Cartagena; Anne Marie Bombassaro; Seyed M. Hosseini-Moghaddam (Canadian Journal of Infectious Diseases and Medical Microbiology)
Ramsay Hunt syndrome associated with varicella zoster virus reactivation affecting the central nervous system is rare. We describe a 55-year-old diabetic female who presented with gait ataxia, right peripheral facial palsy, and painful vesicular lesions involving her right ear. Later, she developed dysmetria, fluctuating diplopia, and dysarthria. Varicella zoster virus was detected in the cerebrospinal fluid by polymerase chain reaction. She was diagnosed with Ramsay Hunt syndrome associated with spread to the central nervous system. Her facial palsy completely resolved within 48 hours of treatment with intravenous acyclovir 10 mg/kg every 8 hours. However, cerebellar symptoms did not improve until a tapering course of steroid therapy was initiated.